Effects of Aging on the Tensile Properties of Polyethylene Fiber-Reinforced Alkali-Activated Slag-Based Composite - Jeong-Il Choi; Se-Eon Park; Su-Tae Kang; Bang Yeon Lee (Advances in Materials Science and Engineering)
Information on the effect of age on the tensile behavior of fiber-reinforced alkali-activated slag-based composite is fairly limited. Therefore, the purpose of this study is to experimentally investigate the effect of age on the compressive strength and tensile properties of the fiber-reinforced alkali-activated slag-based composite. A binder including slag and alkali activators, chemical admixtures, and a reinforcing fiber were selected, and the mixture proportion was determined to make a fiber-reinforced alkali-activated slag-based composite with high ductility. Compressive strength and tensile strength tests were performed, and values were measured at 3, 5, 7, 14, 28, and 90 days. Test results showed that the compressive strength increased as the age increased. Although the first-cracking strength increased like the compressive strength, the increases of tensile strength and tensile strain capacity were not significant compared with those of compressive strength and first-cracking strength.